IMPROVING STUDENT'S VOCABULARY MASTERY BY USING OSTENSIVE MEANS (A CLASSROOM ACTION RESEARCH AT THE FOURTH YEAR OF SD NEGERI 4 SAMBI, BOYOLALI IN 2010/2011 ACADEMIC YEAR) - NURJANAH, ANITA MEI (2011)
This research is aimed at describing the implementation, knowing the result, and finding the strengths and weaknesses of improving student's vocabulary mastery by using ostensive means to the fourth year students of SD Negeri 4 Sambi, Boyolali in 2010/2011 Academic Year. In this research, the writer carries out an action research. The action procedures are planning, acting, observing, and reflecting. In the classroom action research, the writer uses test, observation, interview, and collaborates them to collect the data. There are two kinds of data such as qualitative and quantitative. The sources of the data are the activity of improving the vocabulary mastery using ostensive means, the English teacher and the students as informant, the teacher's lesson plan, the text books (materials), attendance list of the students, etc. The implementation of improving vocabulary mastery using ostensive means consists of the students' achievement in memorizing, pronouncing, and spelling the words. The materials given the teacher are fruits, animals, and activities at home. To know the result of improving vocabulary mastery using ostensive means, the writer gives two kinds of test, namely: pre-test and post-test. The test consists of pronunciation, understanding meaning, and spelling. In pretest, the highest score is 86, lowest score is 20, and mean score is 49.81. In posttest, the highest score is 100, lowest score is 65 and mean score is 83.27. The writer concludes that the students can achieve the target of vocabulary mastery well. The strengths are: the students have a high interest and motivation in teaching-learning process, and they are helped in understanding, pronouncing, and spelling the words. The weaknesses are: the teacher must spend her time and money to get the materials, and need more energy to demonstrate the materials.